Low power and low voltage circuit design with the FGMOS transistor - Rodriguez-Villegas, Esther (London, United Kingdom Institution of Engineering and Technology, 2006)
This book demonstrates FGMOS transistors can be used in a low voltage and low power design context. The techniques shown provide innovative solution, often in situations where the limits of the technology in question have been pushed far below the values recommended by the manufacturer.
Electronic reproduction.
Keywords: Power transistors; Low voltage integrated circuits; Electronic books